Dose-response regulation system for improving renal injury in diabetic nephropathy by buckwheat hull flavonoids. (November 2019) - Tang, Yufang; Li, Tianzhu; Peng, Long; Liu, Junmei; Wang, Yuhua; Piao, Chunhong
Graphical abstract: Highlights: Flavonoids from buckwheat hull (BHF) significantly improved diabetic nephropathy (DN) in db/db mice. The mechanism of BHF therapeutic effect in diabetic nephropathy is related to intervention dose. Reduce of lysine succinylation, acetylation and crotonylation in kidney protein is new target for treatment of DN. Abstract: Diabetic nephropathy (DN) is the most devastating for patients' quality of life and survival. In this study, biochemical indicators and differences in protein expression by proteomics analysis and post-translational modifications (PTMs) of kidney of db/db mice were determined at low (LBHF, 10 mg/kg), middle (MBHF, 30 mg/kg) and high (HBHF, 60 mg/kg) Buckwheat hull flavonoids (BHF) doses intervention for 9 weeks. The results showed that BHF can significantly reduce SCr, SUA, IL-6 and IL-1β levels. Proteomics analysis revealed that the down-regulated differentially expressed proteins (DE protein) in the MBHF group were moreover 2 times than that in LBHF and HBHF group. BHF significantly down-regulated the pathway associated with the Immune system, Transport and catabolism, Environmental information processing. Decreasing lysine succinylation, acetylation and crotonylation of kidney protein were detected significantly in the MBHF group. In conclusion, BHF may be a potential natural product candidate for the effective treatment of DN.